The Biblical Ethic of Free Market Exchange - Degner, Jeffery (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
Despite the calls of ‘Christian Socialists’ to bring market forces under the control of the state and its temporal power, the supreme text of Christianity not only supports the existence of free markets, it also prescribes their existence and operation as the normal, God-given means of social interaction. Both the Old and New Testaments of the Bible provide an ethical defense of the market itself, the division of labor, the principle of voluntary exchange, and the condemnation of force, fraud, and coercion. As the introduction of force into society and exchange is always and ever the policy of interventionists and socialists, the aim of this paper is to oppose those doctrines on the grounds of Biblical ethics. This is not to dismiss the pragmatic, historic, or epistemological failings of the interventionists. The dismantling of socialism on these grounds has been thorough and devastating as provided by the Austrian school of economics. This work provides a moral and ethical ground that not only dismisses the socialist agenda, but adds to an already robust body of work that rejects its interventions due to its inefficiencies, failed states, and its pretense of knowledge.